ANALYSIS OF THE INFLUENCE OF TRADE CREDIT INSURANCE SERVICES, GOVERNMENT SUPPORT AND ENTREPRENEURIAL ORIENTATION ON THE PERFORMANCE OF EXPORT UMKM (STUDY ON TRADE FINANCE SERVICES OF PT. BANK RAKYAT INDONESIA (PERSERO) TBK FOR EXPORT MSMES IN CENTRAL JAVA - Gigieh Perkasa; Yoestini Yoestini (Journal of Economic, Bussines and Accounting (COSTING), 2024)
In this study there are several factors considered as important contributors for SME business growth, the internal factor is the entrepreneurial mindset, while the external factor is government support and financial institution support. The entrepreneurial mindset refers to the mindset, attitude, and perspective possessed by MSME business actors to see opportunities and challenges in the dynamics of business competition that must be faced with creativity and innovation. This mindset is very important for business actors in general because it will affect the way they make decisions, act, and face risks and failures. The government as a regulator and policy maker certainly has a strategic role in the development of MSMEs in Indonesia. MSMEs are an important sector in the country's economy because of their significant contribution to employment, national income, and equitable economic development. Here are some of the government's strategic roles in supporting the development of MSMEs, including simplifying regulations and supporting policies, providing infrastructure, legal protection, and expanding market access. Financial institutions, especially banks, also provide important contributions to the development of MSME businesses, not only limited to access to financing support, but also in their role in providing financial instruments and creating a payment or transaction ecosystem that not only reduces costs but can also create a sense of security for MSME business actors, especially when related to foreign trade transactions.